HEMATOMA OF THE PROXIMAL NAIL FOLD. REPORT OF 41 CASES - Chang Patricia; Rodas Diaz Cecilia (Our Dermatology Online, 2011)
Background: The proximal fold is an important part of the nail apparatus it contributes to the formation of the nail plate and through the cuticle acts as an impermeable barrier protecting it from any cause.Objective: To know the proximal nail fold hematoma caused by the use of pulse oximeter.Material and Methods: A descriptive study was conducted in 41 patients with proximal nail hematoma secondary to the use of oximetry in patients hospitalized in the Intermediate and Intensive Care Unit at the Hospital General de Enfermedades from December 1, 2007 to December 31, 2010.Results: We studied 41 patients with proximal nail fold hematoma secondary to the use of oximeter, 30 (73.1%) were males and 11 (26.8%) females. The numbers of fingers affected by pulse oximeter were in one digit. 30 (73.1%) cases, in two digits 6 (14.6%), in three digits 3 (7.3%), in 4 digits 1 (2.4%) and in 5 digits 1 (2.4%) case. The most affected proximal nail fold was right index: 24 (58.5%), right middle 11 (26.8%), right ring 6 (14.6%), left index 12 (29.2%), and left middle 6 (14.6%) cases.Conclusions: Hematomas of the proximal nail fold may be caused by different traumatisms. The use of pulse oximeter is one of them.